Adjuvants for immunotherapy - Pfaar, Oliver; Cazan, Dorotheea; Klimek, Ludger; Calderón, Moisés A. (Current opinion in allergy and clinical immunology, 2012)
Purpose of review: This article gives an overview about the current state of preclinical and clinical studies using different kinds of adjuvants and their effect on allergen-specific immunotherapy (SIT). Recent findings: Recently, vectors such as liposomes and microspheres and adjuvants such as Toll-like-receptor agonists [e.g. nonmethylated cytosine-guanine dinucleotide (CpG) motifs derived from bacterial DNA or monophosphoryl lipid A (MPL A)] have been used in clinical phase II and III trials demonstrating encouraging clinical effects. Summary: SIT has been optimized for more than 100 years with different approaches. Among these, adjuvants have been shown to amplify the effect of SIT by modulating the immune response to this therapy. In the first part, this article reviews the immunological mechanisms underlying the use of adjuvants targeting key cells of the innate immune system such as dendritic cells. In the second part, it overviews first clinical trials which have been reported so far in both subcutaneous and sublingual allergen-specific immunotherapy investigating the therapeutic potential of adjuvanted extracts. Most of these clinical trials revealed both clinical efficacy and immunological effects. However, more studies are warranted to further focus the specific role of adjuvants in the process of tolerance induction in allergic patients.
Gesehen am 20.06.2018
Originally published: December 1, 2012